Outcome of early vs. late tracheostomy in traumatic brain injury patients admitted to neurosurgery ICU - Adhikari, Ganesh; Kumar Das, Bibek; Shrestha, Ajit (Journal of Chitwan Medical College, 2025)
Introduction: Tracheostomy is one of the most commonly done procedures in patients with severe head injury. The study was carried out to evaluate the role of early tracheostomy and outcomes in patients with severe traumatic brain injury (TBI). Method: This study compared early and late tracheostomy in TBI patients in neurosurgical ICU at Chitwan Medical College, Nepal, from Apr 2019 to Jul 2022. Data were extracted from medical records. Tracheostomy at admission or mortality <3 days of admission were excluded. Ethical approval was taken. Tracheostomies done ≤7 days of admission were considered early tracheostomies (ET), and >7 days late (LT). Length of ICU stay, hospital stay, injury types, admission GCS, diagnosis and outcome between ET and LT were compared. Continuous variables presented as mean±SD were analysed using t-tests, while categorical variables summarised as frequency percentages were analysed with X² tests. The IBM SPSS 26.0 was used for analysis, and p≤0.05 was considered statistically significant. Result: Out of 76 patients with TBI admitted to neurosurgical ICU who underwent tracheostomies, 50(65.8%) were ET and 26(34.2%) LT. The ET was associated with shorter ICU stay (p<0.013). Mortality and other outcomes had no significant difference between ET and LT groups. Conclusion: Early tracheostomy was beneficial in terms of a significant decrease in ICU stays compared to late tracheostomy. Timing of tracheostomy did not significantly affect other outcomes.